Homoeopathy for the Management of Delusional Disorder: A Case Report - Moorthi, S. Karunakara; K.C, Manu Chandran (Homœopathic Links, 2024)
Introduction Delusions, a core symptom of psychosis, are false beliefs that are rigidly held with strong conviction despite contradictory evidence. Persistent delusions if held for more than 1 month lead to the diagnosis of delusional disorder (DD) as per the Diagnostic and Statistical Manual of Mental Disorders-5. Very sparse literature is available evaluating the utility of individualised homoeopathic medicine in this condition.Materials and Methods A 60-year-old man presenting with symptoms of DD was treated during the period of February 2020 to February 2021. Individualised homoeopathic medicine was prescribed. Outcomes were assessed using Psychotic Symptom Rating Scales. Modified Naranjo Criteria was used to assess whether the changes were likely to be associated with the homoeopathic intervention.Results A beneficial result was obtained from Individualised homoeopathic treatment.Conclusion Even though this is a single case report, the recovery of the patient from the suspiciousness is remarkable and there is no relapse of the symptoms. The patient's family life is peaceful now and he was able to rejoin his job.
Keywords: delusional disorder; delusion; homoeopathy; PSYRATS; Stramonium; Nux vomica